Haemoglobin C and S role in acquired immunity against Plasmodium falciparum malaria. - Verra, F; Simpore, J; Warimwe, G; Tetteh, K; Howard, T; Osier, F; Bancone, G; Avellino, P; Blot, I; Fegan, G; Bull, P; Williams, T; et al. (Public Library of Science, 2007)
A recently proposed mechanism of protection for haemoglobin C (HbC; beta6Glu-->Lys) links an abnormal display of PfEMP1, an antigen involved in malaria pathogenesis, on the surface of HbC infected erythrocytes together with the observation of reduced cytoadhesion of parasitized erythrocytes and impaired rosetting in vitro. We investigated the impact of this hypothesis on the development of acquired immunity against Plasmodium falciparum variant surface antigens (VSA) encoding PfEMP1 in HbC in comparison with HbA and HbS carriers of Burkina Faso. We measured: i) total IgG against a single VSA, A4U, and against a panel of VSA from severe malaria cases in human sera from urban and rural areas of Burkina Faso of different haemoglobin genotypes (CC, AC, AS, SC, SS); ii) total IgG against recombinant proteins of P. falciparum asexual sporozoite, blood stage antigens, and parasite schizont extract; iii) total IgG against tetanus toxoid. Results showed that the reported abnormal cell-surface display of PfEMP1 on HbC infected erythrocytes observed in vitro is not associated to lower anti- PfEMP1 response in vivo. Higher immune response against the VSA panel and malaria antigens were observed in all adaptive genotypes containing at least one allelic variant HbC or HbS in the low transmission urban area whereas no differences were detected in the high transmission rural area. In both contexts the response against tetanus toxoid was not influenced by the beta-globin genotype. These findings suggest that both HbC and HbS affect the early development of naturally acquired immunity against malaria. The enhanced immune reactivity in both HbC and HbS carriers supports the hypothesis that the protection against malaria of these adaptive genotypes might be at least partially mediated by acquired immunity against malaria.